Ex-ante volatility measures based on agents' expectations. An application to Argentina's tems of trade - Buzzi, Sergio Martín (2017)
Fil: Buzzi, Sergio Martín. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.